PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SENI BUDAYA MATERI MSENI RUPA SISWA KELAS VII SMP NEGERI 30 PADANG - DIPO SUSILO, Drs. Suib Awrus, M.Pd., Dra. Zubaidah, M.Pd. (Serupa The Journal of Art Education, 2019)
The purpose of this research is to know the difference between the results of student learning that is treated with a model of discovery learning with classes that are treated with conventional learning model of fine art material class VII Junior High School 30 Country of Padang. This type of research is research experiments with design research Equivalent Control Group Design. The sample in this research is the 64 students i.e. Class VII. 5 and VII. 3, each numbering 32 learners, with a population that is the entire class VII Junior High School 30 Country of Padang. The collection of data in this study uses the tests to measure learning outcomes learner and processed through the program SPSS v.16.0. Based on the hypothesis test results retrieved can be concluded that there is a significant difference between the results of the study the learners with the use of a model of discovery learning and learning outcomes students use learning model conventional learning material culture art art learners Class VII Junior High School 30 Country of Padang. Researchers suggest for schools and teachers, especially teachers of art and culture to implement or try using a model of learning by discovery learning.Keywords: Discovery learning, Konvensional, Hasil Belajar